2020
DOI: 10.31234/osf.io/k8ynt
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Correct responses alleviate the negative evaluation of conflict

Abstract: Recent studies have demonstrated that cognitive conflict, as experienced during incongruent Stroop-trials, is automatically evaluated as negative in line with theories emphasizing the aversive nature of conflict. However, while this is well-replicated when people only see the conflict stimuli, results are mixed when participants also respond to stimuli before evaluating them. Potentially, the positive surprise people feel when overcoming the conflict, allows them to evaluate the experience as more positive. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
1
0
1
Order By: Relevance
“…Particularly, when levels of irrelevant capture shift over time, our normative model simulations showed that one should adapt their decision boundary in response to these changes to compensate for the newly available potential reward rate. However, our results do not suggest that such subjective estimates (e.g., conflict aversiveness) directly promote strategic adaptations (aligning perhaps with mixed findings regarding the role of subjective estimates in guiding trial-by-trial adaptations [57][58][59] ). Instead, we found that conflict aversiveness indirectly guides adaptations of the decision boundary through feelings of exerted effort, frustration and fatigue.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Particularly, when levels of irrelevant capture shift over time, our normative model simulations showed that one should adapt their decision boundary in response to these changes to compensate for the newly available potential reward rate. However, our results do not suggest that such subjective estimates (e.g., conflict aversiveness) directly promote strategic adaptations (aligning perhaps with mixed findings regarding the role of subjective estimates in guiding trial-by-trial adaptations [57][58][59] ). Instead, we found that conflict aversiveness indirectly guides adaptations of the decision boundary through feelings of exerted effort, frustration and fatigue.…”
Section: Discussioncontrasting
confidence: 73%
“…Particularly, when levels of irrelevant capture shift over time, individuals must adapt their decision boundary in response to these changes to compensate for the newly available potential reward rate, as demonstrated by our simulations. However, our results do not show that such subjective estimates (e.g., conflict aversiveness) necessarily promote strategic adaptations (aligning with mixed findings regarding the role of subjective estimates in guiding trial-by-trial adaptations 5759 ). Instead, we found that the metacognitive experiences of frustration and fatigue were more closely related to strategic changes.…”
Section: Discussionsupporting
confidence: 51%